Pemahaman Nadzir Terhadap Sertifikasi Tanah Sebagai Perlindungan Hukum Asset Wakaf - zulfa, diah (Al-Hukkam: Journal of Islamic Family Law, 2023)
The people of Randudongkal Village, who are predominantly Muslim, have been passed down from generation to generation in terms of the management of waqf land, which is used for both social and religious activities. This also affects their spirit in religion, which makes waqf land a place that must be managed properly and of course its existence must be protected. The problem faced today is the lack of understanding of them as nadzir who do not fully understand the importance of caring for and protecting assets from waqf objects and assets as an effort to maintain the mandate of wakif to be managed.The formulation of the problem in this study is how is Nadzir's understanding of land certification as legal protection for waqf assets in Randudongkal Village? How is the management of waqf land in Randudongkal Village?,This research is a field research (field research). While the approach used in this study is a qualitative approach. Methods of data collection using interview techniques, observation and documentation.Then for the data analysis technique using the analysis of the interactive model analysis technique from Miles and Huberman.The results of this study indicate that the majority of Nadzir's understanding of waqf land certification as legal protection of waqf assets in Randudongkal Village is good, and the management of waqf land in Randudongkal Village is good, although there are.